ANTIATHEROSCLEROTIC AND ANTIOXIDANT POTENTIAL OF PETROLEUM ETHER EXTRACT OF PROSOPIS CINERARIA POD IN HYPERCHOLESTEROLEMIC RABBITS - NOOPUR JAIPAL; HEERA RAM (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The present study is done to investigate the anti-atherosclerotic efficacy of petroleum ether extract of Prosopis cineraria pod in hypercholesterolemic diet-induced atherosclerosis in rabbits. Methods: Atherosclerosis was induced in rabbits by feeding normal diet supplemented with oral administration of cholesterol (500 mg/kg body weight/day) which was mixed in coconut oil for 15 days. Rabbits were then administered with petroleum ether extract of P. cineraria pod for 45 days (Group III), and another set of the group was treated with standard drug Atorvastatin for 45 days. After the completion of the experimental period, the serum biochemistry and histological analysis of thoracic aorta was done. Along with it lipid peroxidation(LPO) and antioxidant parameters such as catalase (CAT), superoxide dismutase (SOD), and ferric reducing ability of plasma (FRAP) were estimated. Results: There was a significant increase (p≤0.001) in serum total cholesterol (TC), low density lipoprtein (LDL) and triglycerides after cholesterol feeding when compared with the control group (Group I). Antioxidant parameters were altered too with an increased serum LPO while the reduction in CAT, SOD, and FRAP was observed. After the administration of the petroleum ether extract, significant reduction in TC, LDL-C, very low-density lipoprotein -C, and triglyceride was observed as compared to high-fat diet control rabbits. Slightly significant reduction in (p≤0.05) atherosclerotic plaque in the aorta was observed while cardiac LPO was lowered alternatively CAT, SOD, and FRAP levels increased in petroleum ether extract administered rabbits. Conclusion: The outcomes from this study recommend that P. cineraria pod extract has hypocholesterolemic effect thereby controlling atherosclerosis and has potent antioxidant activity which may be responsible for improving the lipid profile.